Formulation Development and Evaluation of New Albendazole Tablets with Integrated Quality by Design (QbD) Approach - Sitre, Dnyaneshwar G; Kamble, Ravindra K. (Journal of Drug Delivery and Therapeutics, 2021)
Hydatid disease occurs in most areas of the world and currently affects about one million people. Albendazole is an orally administered broad spectrum anthelmintic drug approved by US FDA in 1996. Literature review suggests Albendazole is low solubility compound and most of the studies were performed to improve the solubility with traditional approach of product development. The present study was aimed to apply Design of Experiments (DoE) in the development and optimization of drug release from new Albendazole tablets using three factor two level (23) full factorial designs with integrated Quality be Design (QbD) approach. New Albendazole tablets were formulated using micronized grade of the Albendazole active and excipients were selected inline with market reference product. Quality target product profile (QTPP) and Critical quality attributes (CQAs) were designed. Risk assessment was used to identify the Formulation variables impacting CQA dissolution. The amount of Formulation variables were optimized on the basis of drug release profiles at 15 minutes and 30 minutes of different formulation batches manufactured based on 23 full factorial design. Tablets were prepared by wet granulation technique and evaluated for various physicochemical parameters and in vitro drug release. Formulation trials dissolution results at 15 minutes and 30 minutes were evaluated to derive the concentration of Formulation variables which will achieve the release of more than 80%. Analysis of variance (ANOVA) analysis, Pareto chart and Contour plot were used to predict the values of formulation variables and their effect on dissolution.  Updated risk assessment of the Formulation Variables was performed and justification was provided for reduction of risk from medium to low level. Optimized formulation from DOE had comparable dissolution profile with market reference tablet. Stability studies of new Albendazole tablets 200 mg were conducted at ICH accelerated conditions and found to be stable. Thus studies revealed that full factorial experimental design could efficiently be applied for optimization of formulation variables affecting drug release. New Albendazole tablets 200 mg successfully formulated with application of the integrated quality by design (QbD) and design of experiment (DOE) approach and thereby achieved comparable release profile with market reference product.